(3GdEJUGdGJ GdJShjbjI GdEdcJQhfjI(B((3eONd JMdjdj (B/s - (3GdYdGb, HTjQ YHGSs ((3YeGf(B: s (3eDSSI GdhQGb(B, s, 2005)
(3GdEJUGdGJ GdJShjbjI(B-(3UfGYI GdEJUGdGJ(B-(3GJUGdGJ GdJShjb GdOGNdj(B-(3GdEJUGdGJ GdJShjbjI GdJaGYdjI hOhQ JbfjGJ GdeYdheGJ hGdEJUGd aj JaYjdgG(B-(3OhQ JbfjGJ GdeYdheGJ hGdEJUGdGJ aj JTcjd YfGUQ GdEJUGdGJ GdJShjbjI(B-(3hSGFd GdEJUGdGJ GdehLgI ef TNU Edi BNQ aj GdeSJbHd GdJaGYdj(B-(3GSJNOGe bOQGJ GdCfJQfjJ dCZQGV GdJQhjL ef bHd GdTQcGJ GdhGbYjI h GdEaJQGVjI(B-(3EfTGA hJQhjL GdehbY GdTHcj(B-(3HQeLjGJ hCLgRI hYJGO GdEJUGdGJ GdJShjbjI GdQbYjIs
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs